2015
DOI: 10.1186/s40729-015-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Current status of implant prosthetics in Japan: a survey among certified dental lab technicians

Abstract: BackgroundThere are many implant cases in which dental technicians take initiative with regard to the design of implant prostheses, and to a certain extent, this area of care is one in which dentists do not necessarily play the leading role. Moreover, inadequate communication between dental technicians and dentists and insufficient instructions for technicians has been highlighted as issues in the past. The purpose of this questionnaire is to improve the quality of implant prostheses and thereby contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…This result is similar with Al Saleh's study [15] but opposite to Chowdhary's study [10] where the cement-retained prosthesis was the favorite restoration of most of the dentists across the countries surveyed. Furthermore, the percent obtained for the lab Romanian professionals is different from the Japanese study [13] where 61.4% of the technicians declare a higher demand for cement-retained restorations.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…This result is similar with Al Saleh's study [15] but opposite to Chowdhary's study [10] where the cement-retained prosthesis was the favorite restoration of most of the dentists across the countries surveyed. Furthermore, the percent obtained for the lab Romanian professionals is different from the Japanese study [13] where 61.4% of the technicians declare a higher demand for cement-retained restorations.…”
Section: Discussioncontrasting
confidence: 64%
“…The situation is quite different from the study from Saudi Arabia, wherein 49% of the cases the dentist is managing the treatment plan [14]. In Hagiwara 's study from 2015 [13] 39.3% assign the doctor as a leader, whereas 28.9% of the respondents' report that there is a doctortechnician teamwork. However, due to the fact that dental technicians have claimed in this study also that in 14.5% of the cases they step forward, some problems concerning the doctor's training in implant restoration treatment planning arise.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Hagiwara et al. sent questionnaires to 120 out of 285 certified dental laboratories in Japan and identified that PFM was the most commonly reported material used for FIP in the anterior and posterior region, 43% and 31%, respectively, followed by Zirconia 27% and 14%, respectively [ 37 ]. These results must be interpreted with caution because of the high exclusion rate in that study, which could affect the outcome as well as the earlier mentioned difficulty with inadequate material information.…”
Section: Discussionmentioning
confidence: 99%
“…First issue had authors from Germany, Japan, USA, Sweden, India, and Netherlands. [20][21][22][23][24][25] The articles are published every month, and they are published as they are prepared (Table 7). The most robust year in development was 2017 when 50 articles have been published (Table 1).…”
Section: Yearsmentioning
confidence: 99%